A pre-clinical MRI-guided all-in-one focused ultrasound system for murine brain studies - Tarana Parvez Kaovasia; Sarah Duclos; Dinank Gupta; Kourosh Kalayeh; Mario Fabiilli; Douglas C. Noll; Jonathan Sukovich; Aditya Pandey; Zhen Xu; Timothy L. Hall (Scientific Reports)
Abstract This paper describes the design and initial proof-of-concept of a single pre-clinical transcranial focused ultrasound (FUS) system capable of performing histotripsy (mechanical ablation), hyperthermia, blood-brain barrier opening (BBBO), sonodynamic therapy, or neuromodulation in a murine brain. We have termed it the All-in-One FUS system for murine brain studies, which is the first FUS system of its kind. The 1.5 MHz ultrasound transducer was fabricated and driven using a custom electronic driver to produce 3-cycle pulses with a focal peak-negative pressure (P-) of up to 87 MPa at a low duty cycle (< 0.1%) for histotripsy as well as 50% duty cycle pulsed-ultrasound with a spatial-peak temporal-average intensity (Ispta) of up to 251 W/cm2 for the other FUS modalities. This All-in-One system can be guided by MRI or stereotactically to maximize its flexibility. To validate the design of the system, histotripsy, BBBO, and hyperthermia were performed in naïve brains of two mice for each modality. Histotripsy and BBBO were performed using MRI-based stereotactic co-registration. The therapeutic effect was confirmed using T2-weighted MR-images for histotripsy, and T1-weighted Gadolinium contrast-enhanced MR-images for BBBO. For hyperthermia, an MRI-compatible insert was designed to fit inside the 80 mm imaging coil of a 7-Tesla small-animal MRI-system, with T2-weighted MR-images used to confirm targeting, and MR-thermometry used to monitor the thermal dose delivered.